Cardiac Graft from Donors with Extracorporeal Support—A Report of Two Cases - Panholzer, Bernd; Huenges, Katharina; Cremer, Jochen; Haneya, Assad (The Thoracic and Cardiovascular Surgeon Reports, 2018)
The persistent global shortage of organ donors is still a major limitation for transplantation. Experiences of heart transplantation from donors with extracorporeal support are rare. Here, we report from two cases of donors who were supported by extracorporeal membrane oxygenation due to acute circulatory failure. In both cases, the direct postoperative course was uneventful and free from major complications. The patients were discharged to a rehabilitation clinic. Our experience suggests that the use of heart organ from carefully selected donors with extracorporeal support is possible and may lead to an excellent outcome.
Keywords: extracorporeal support; heart transplantation; organ donors